The effect of protein intake, physical activity and gender on cognitive function in the elderly at Surakarta Health Center - Indry Wulansari; Brian Wasita; Muthmainah Muthmainah (AcTion: Aceh Nutrition Journal, 2024)
The prevalence of cognitive function impairment increased from 2010 to 2020. Cognitive function declines in the form of memory, language, and action disorders. Cognitive function can be prevented by consuming protein and engaging in physical activity. This study aimed to determine the effect of protein intake on neurotransmitter synthesis, physical activity to increase brain protein, and sex related to metabolism on cognitive function in the elderly at Surakarta Health Center. The research design used observational analytics, with a cross-sectional approach. The research location at several health centers namely in Pajang, Jayengan, Gajahan, Sibela and Gambirsari. This study was conducted from January to February 2024. The sample was obtained by purposive sampling of 110 elderly people at the Surakarta City Health Center. Research data were obtained through interviews with a protein intake questionnaire (SQFFQ), physical activity questionnaire (IPAQ), and cognitive function questionnaire using the Mini Mental State Examination questionnaire, which has been tested for validity and reliability. Data analysis was performed using the Ordinal Logistic Regression Test, with a 95% confidence interval (CI). The results showed that protein intake, physical activity, and sex had no effect on cognitive function (p>0,05). This was due to other factors that were not examined in this study. In conclusion, the decline in cognitive function can be improved by protein intake, which is related to neurotransmitters, and physical activity that is routinely performed can help proteins in the brain increase.